QUR'AN MEMORIZATION CURRICULUM MODEL AT BOARDING-BASED UNIVERSITIES - Sa'adah, Umi; Rosyada, Dede; Sapiudin, Sapiudin (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This research aims to uncover: 1). The history of boarding campuses; 2). The Qur'an memorization curriculum model at boarding-based universities (IIQ, PTIQ, and IDAQU); 3). Methods and techniques for learning and memorizing the Qur'an for boarding students; 4). Supporting and inhibiting factors for implementing the Qur'an memorization curriculum, its evaluation, and its influence on the achievement of boarding students. This research methodology uses a qualitative approach and focuses on the Al-Qur'an memorization curriculum model, namely by examining naturally occurring phenomena as a direct data source. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies as supporting information. The informants in this study were the head of the tahfidz institution as a key informant, institutional staff, tahfidz instructors, Islamic boarding school/ma'had administrators, and students. Data analysis techniques were carried out using qualitative analysis, consisting of data reduction, data display, and verification or drawing conclusions. These three activities are interrelated with each other. The research found the following results: First, IIQ was founded in 1977, PTIQ in 1971, and IDAQU in 2020. Second, the three boarding-based universities have different tahfidz curriculum models: IIQ Jakarta offers 5, 10, 20, and 30 Juz programs; PTIQ offers 30 Juz (full tahfidz), 3 Juz (limited tahfidz), and 1 Juz (employee class); and IDAQU categorizes studentsas mubtadi (beginner), mutawassit (intermediate), and mahir (advanced). Third, the primary Qur'an memorization learning method at all three boarding campuses is recitation. Fourth, both supporting and inhibiting factors exist in Qur'an memorization. A gradual/tiered memorization curriculum model can assist students in fulfilling their dual obligations of Qur'an memorization and academic studies. These findings offer a replicable framework for other higher education institutions seeking to integrate Qur'an memorization into their academic programs, particularly in boarding-based settings.